Acoustic conditions in open plan office - Application of technical measures in a typical room - Witold Mikulski (Nofer Institute of Occupational Medicine, 2018)
Background Noise in open plan offices should not exceed acceptable levels for the hearing protection. Its major negative effects on employees are nuisance and impediment in execution of work. Specific technical solutions should be introduced to provide proper acoustic conditions for work performance. Material and Methods Acoustic evaluation of a typical open plan office was presented in the article published in "Medycyna Pracy" 5/2016. None of the rooms meets all the criteria, therefore, in this article one of the rooms was chosen to apply different technical solutions to check the possibility of reaching proper acoustic conditions. Acoustic effectiveness of those solutions was verified by means of digital simulation. The model was checked by comparing the results of measurements and calculations before using simulation. Results The analyzis revealed that open plan offices supplemented with signals for masking speech signals can meet all the required criteria. It is relatively easy to reach proper reverberation time (i.e., sound absorption). It is more difficult to reach proper values of evaluation parameters determined from A-weighted sound pressure level (SPLA) of speech. The most difficult is to provide proper values of evaluation parameters determined from speech transmission index (STI). Finally, it is necessary (besides acoustic treatment) to use devices for speech masking. The study proved that it is technically possible to reach proper acoustic condition. Conclusions Main causes of employees complaints in open plan office are inadequate acoustic work conditions. Therefore, it is necessary to apply specific technical solutions - not only sound absorbing suspended ceiling and high acoustic barriers, but also devices for speech masking. Med Pr 2018;69(2):153-165